Adaptação transcultural do “Wheelchair Skills Test” (versão 4.3) - questionário para usuários de cadeiras de rodas manuais e cuidadores para a língua portuguesa (Brasil) - Campos, Lays Cleria Batista (2017)
Introduction: The Wheelchair Skills Test Questionnaire is a tool that measures the functional mobility in different environments and that can contribute to improving the skills of people in wheelchairs reflecting on trust, safety and independence. In Brazil, there is a gap of assessment, encompassing the use of assistive technology and functional mobility at the level of the necessary skills in the daily lives of people who use wheelchairs and caregivers. Objective: Cross-cultural adaptation of Wheelchair Skills Test Questionnaire (WST-Q), version 4.3 for manual wheelchair users and caregivers, to Portuguese language (Brazil). Methodology: The methodological procedure involved the steps of: 1) translation; 2) back translation; 3) analysis by a committee of experts; 4) pretest according to international guidelines. Results: The version was assessment by 15 wheelchair users and 15 caregivers. In total 8 out of 30 participants presented suggestions to facilitate an understanding of the target audience. The instrument is displayed for easy understanding. Conclusion: The participants approved the WST-Q 4.3 as useful in the Brazilian reality. It is recommended to evaluate the measurement properties for a version in a representative sample.